Effectiveness of “How to Write a Sentence” as Instructional Material to Improve the Writing Skills of Grade 6 Pupils - Apolonio, John Noah B. (Future Science / FSH-PH Publications, 2023)
As students’ progress in their studies, they must learn a variety of important skills. Among these is writing, which is undeniably one of the most important skills that every student must develop. However, writing has always been a major challenge for students learning English, particularly in elementary schools and for second language learners. This study determined the effectiveness of the instructional material